COLLOCATIONS AND THEIR IMPORTANCE IN LANGUAGE STUDY - Sevara Saidqulova; Gulkhayo Shukurova; Hakima Abdullajonova (TADQIQOTLAR, 2025)
Abstract Collocations — habitual and predictable word combinations — represent one of the most crucial yet often underappreciated aspects of linguistic competence. Mastery of a language extends beyond grammatical accuracy and vocabulary size; it involves the intuitive understanding of how words naturally co-occur within authentic contexts. This paper examines the theoretical underpinnings of collocations, their linguistic classifications, and their indispensable role in language acquisition, fluency, and pedagogical application. Drawing upon insights from corpus linguistics, cognitive linguistics, and applied language studies, the paper argues that collocational awareness bridges the gap between formal linguistic knowledge and communicative competence. It discusses how collocations contribute to the naturalness, idiomaticity, and efficiency of communication, and how their neglect in language pedagogy leads to fossilized errors and non-native-like production. Emphasis is placed on integrating collocation learning into vocabulary instruction and communicative teaching frameworks. The paper concludes that collocational competence should be prioritized as a central component of language study and curriculum design to produce learners who not only know a language but can also live it fluently.